Hybrid Method for Optimal Placement of Multiple SPV Based Multiple RDGs in Microgrid System - Samir M. Dawoud; Xiangning Lin; Firas M. F. Flaih; Qasim Kamil Mohsin (Institute of Advanced Engineering and Science, 2016)
A hybrid method has been suggested for optimal placement of multiple renewable distribution generations (RDGs) in microgrid system. The analytical approaches have not been appropriated for optimal placements of multiple solar photovoltaic (SPV) based on RDGs alone. In this work, hybridization of a fuzzy method and particle swarm optimization (PSO) search for the optimal placement of multiple RDGs in microgrid systems for decreasing the active power loss has been proposed. In this approach, the sizes of RDGs are evaluated at every bus by PSO method while the locations are determined by fuzzy based technique. The objective function (OBF) has been minimized under operating constraints. The improvements in nodal voltage profile have been observed. To confirm the proposed hybrid approach, results have been compared with bat algorithm (BA) technique and existing fast improved analytical (IA) method results. The suggested technique has been tested on 33-bus and 69-bus microgrid system.